1994
DOI: 10.1128/aem.60.8.2759-2765.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium and zinc on attachment and detachment interactions of Pseudomonas fluorescens H2 with glass

Abstract: The physiological and physicochemical bases for the effect of 5, 10, 50, or 100 ,ug of Cd and Zn ml-' on the attachment and detachment interactions of Pseudomonasfluorescens H2 with glass substrata were determined. Attachment and detachment varied with the type and concentration of metal and the time at which cells were exposed to the metal. The largely inhibitory effect of the metals on bacterial motility and physiological activity did not directly influence attachment. The amount of Cd or Zn accumulated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Previous research suggested that attachment of Pseudomonas £uorescens H2 to glass surfaces a¡ected subsequent accumulation of Cd 2 [5]. The aim of this study was to determine the in£uence of attachment to glass surfaces on the uptake of heavy metal cations by P. £uorescens H2.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous research suggested that attachment of Pseudomonas £uorescens H2 to glass surfaces a¡ected subsequent accumulation of Cd 2 [5]. The aim of this study was to determine the in£uence of attachment to glass surfaces on the uptake of heavy metal cations by P. £uorescens H2.…”
Section: Introductionmentioning
confidence: 95%
“…P. £uorescens H2 (wild-type strain) [15] was maintained on glucose minimal medium (GMM) (pH 7) solidi¢ed with 1% (w/v) pure agar, as previously described [5]. Cultures were stored at 4³C.…”
Section: Bacterial Strain and Storage Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesiveness to surfaces was assessed by suspending glass slides vertically in 100 ml DCM at 25°C for 24 h. Attached cells were enumerated microscopically by staining (McEldowney 1994). Colony-forming units in suspension were enumerated as described above and the relative percentage adhesion calculated.…”
Section: Determination Of Adhesion Of Bacteria Isolated From Biofilmsmentioning
confidence: 99%